Response quality of e-mail inquiries-A driver for knowledge management in the tourism organization? - Zehrer, A.; Pechlaner, Harald (2013)
The growing world-wide competition of tourism regions, changing demand patterns, the claim for better products and offers, the decreasing attractiveness and increasing uniformity of offers consistently lead to new challenges for the quality assurance of destinations. High service quality enables tourism entrepreneurs to achieve decisive competitive advantages. Quality within a destination comprises all services which the guest is engaged in and is not limited by time or location of the stay. A crucial point is the first contact of a guest with the destination, which happens by e-mail inquiries in the majority of cases. The development of information technology has lead to more and more guests gathering pieces of information via the internet and has induced researchers to study this phenomenon (Buhalis and Licata, 2002; Raman-Bacchus and Molina, 2001). Therefore, response behavior becomes a key factor for the success of tourism organizations (Pechlaner et al. 2002). From the guest's point of view, the speed of response and breadth of information are to be seen as decisive factors for service quality and customer satisfaction. A mystery guest check by means of e-mail inquiries sent to selected tourism organizations was undertaken to determine the response behaviour and breadth of information provided by tourism organizations and to reveal potential gaps in the knowledge management and transfer of these organizations. According to elaborated quality criteria and standards, the paper reports a two-year mystery guest study of tourism organizations of an Alpine destination in Europe. © 2006 by The Haworth Press, Inc. All rights reserved.